Elevation of inositol pyrophosphate IP7 in the mammalian spinal cord of amyotrophic lateral sclerosis - Ito, Masatoshi; Fujii, Natsuko; Kohara, Saori; Tanaka, Masayuki; Takao, Masaki; Mihara, Ban; Saito, Yuko; Mizuma, Atsushi; Nakayama, Taira; Netsu, Shizuka; Suzuki, Naoto; Kakita, Akiyoshi; et al. (Frontiers in Neurology, 2024)
Background Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder associated with progressive impairment of spinal motor neurons. Continuous research endeavor is underway to fully understand the molecular mechanisms associating with this disorder. Although several studies have implied the involvement of inositol pyrophosphate IP7 in ALS, there is no direct experimental evidence proving this notion. In this study, we analyzed inositol pyrophosphate IP7 and its precursor IP6 in the mouse and human ALS biological samples to directly assess whether IP7 level and/or its metabolism are altered in ALS disease state. Methods We used a liquid chromatography-mass spectrometry (LC-MS) protocol originally-designed for mammalian IP6 and IP7 analysis. We measured the abundance of these molecules in the central nervous system (CNS) of ALS mouse model SOD1(G93A) transgenic (TG) mice as well as postmortem spinal cord of ALS patients. Cerebrospinal fluid (CSF) and peripheral blood mononuclear cells (PBMCs) from ALS patients were also analyzed to assess if IP7 status in these biofluids is associated with ALS disease state. Results SOD1(G93A) TG mice showed significant increase of IP7 level in the spinal cord compared with control mice at the late stage of disease progression, while its level in cerebrum and cerebellum remains constant. We also observed significantly elevated IP7 level and its product-to-precursor ratio (IP7/IP6) in the postmortem spinal cord of ALS patients, suggesting enhanced enzymatic activity of IP7-synthesizing kinases in the human ALS spinal cord. In contrast, human CSF did not contain detectable level of IP6 and IP7, and neither the IP7 level nor the IP7/IP6 ratio in human PBMCs differentiated ALS patients from age-matched healthy individuals. Conclusion By directly analyzing IP7 in the CNS of ALS mice and humans, the findings of this study provide direct evidence that IP7 level and/or the enzymatic activity of IP7-generating kinases IP6Ks are elevated in ALS spinal cord. On the other hand, this study also showed that IP7 is not suitable for biofluid-based ALS diagnosis. Further investigation is required to elucidate a role of IP7 in ALS pathology and utilize IP7 metabolism on the diagnostic application of ALS.